Traditionalism of Tolerance in Dayah System: A Reflective Note on the Biography of Abon Aziz Samalanga of Aceh - Ismail Fahmi Arrauf Nasution; Miswari Miswari; Ilham Dwitama Haeba (IAIN Pekalongan, 2020)
This article aims to analyze the value of telerance and deradicalization through local wisdom by contemplating the biography and contribution of Abon Aziz Samalanga. Using a biographical approach, the autor raises the values of tolerance of Abon Aziz through traditional education methods which become his commitments, political attitudes and multicultural values. The findings of this article are systematic and deeply explorative in traditional education in dayah, the role model of daily life taught by involving santri is the capital of tolerance and de-radicalization which is very important to be re-lived by students and the community so as not to be involved in intolerant and radical actions. By contemplating the life of Abon Aziz Samalanga, santri and society do not only have the potential to become tolerant beings but can also be agents of deradicalization.